(-1)^2009+(-3)*|-3/9|--4^3÷(-2)-2^2 +3/4+|-3--4|--(3/2)^3 *25/27
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 10:19:58
(-1)^2009+(-3)*|-3/9|--4^3÷(-2)-2^2+3/4+|-3--4|--(3/2)^3*25/27(-1)^2009+(-3)*|-3/9|--4^3÷(-2)-2^2+3/
(-1)^2009+(-3)*|-3/9|--4^3÷(-2)-2^2 +3/4+|-3--4|--(3/2)^3 *25/27
(-1)^2009+(-3)*|-3/9|--4^3÷(-2)
-2^2 +3/4+|-3--4|--(3/2)^3 *25/27
(-1)^2009+(-3)*|-3/9|--4^3÷(-2)-2^2 +3/4+|-3--4|--(3/2)^3 *25/27
(-1)^2009+(-3)*|-3/9|--4^3÷(-2)
=-1-1-64÷(-2)
=-2+32
=30
-2^2 +3/4+|-3--4|--(3/2)^3 *25/27
=-4+21/4-27/8×25/27
=-4+21/4-25/8
=-4+17/8
=-15/8
=-1+1+6=6
=-4+0.75+7+27/8*25/27=6.875
(-1)^2009+(-3)*|-3/9|--4^3÷(-2)
=-1+(-3)*(1/3)+64/2
=-1-1+32
=-2+32
=30
-2^2 +3/4+|-3--4|--(3/2)^3 *25/27
=-4+3/4+7-27/8*25/27
=-4+21/4-25/8
=-4+17/8
=-15/8
(-1)^2009+(-3)*|-3/9|-(-4^3)÷(-2)
=-1+(-3)*|-1/3|-4^3÷2
=-1+(-1)-32
=-2-32
=-34
-2^2 +3/4+|-3--4|-【-(3/2)^3】 *25/27
=-4+3/4+|-3+4|-(-27/8)*25/27
=-4+3/4+1+27/8*25/27
=-9/4+25/8
=-18/8+25/8
=7/8
1/2009+2/2009-3/2009-4/2009+5/2009+6/2009-7/2009-8/2009+9/2009+10/2009-...-1999/2009-2000/2009+2001/2009+2002/2009
如何计算1-3+5-7+9-11...+2009-2011
1+3+5+7+9+11+…+2009
1-3+5-7+9-11+…+2009-2011
(-1)+3+(-5)+7+(-9)+...+(-2005)+2007+(-2009)=?
1-3+5-7+9-11.2005-2007+2009怎么算
1+3+5+7+9+11+…+2009
-1+3-5+7-9+11...-2009+2011
1-3+5-7+9-11……2007-2009?
数学题1-3+5-7+9-11.+2007-2009
-1+3-5+7-9+11-.-2009+2010=?
-1+3+(-5)+7(-9)+...+2003+(-2005)+2007+(-2009)
1+ 3+ 5 +7+ 9 +.+2003+2005+2007+2009+2011
1-3+5-7+9+.+2009-2011等于多少
-1^2×(-3)^2009×(-2)^2008÷9/2
1+3+5+7+9+11+.2009+2011=?
1+3+5+7+9……+2009等于多少
1/2009+2/2009+3/2009+.+2008/2009=?